SOCIODEMOGRAPHIC CORRELATES OF CONSANGUINEOUS MARRIAGE IN THE MUSLIM POPULATION OF INDIA - R. HUSSAIN and A. H. BITTLES (J. biosoc. Sci. (2000) 32, 433-442, 2000)
Using data derived from the 1992-1993 National Family Health Survey, the sociodemographic characteristics of consanguineous marriage were determined in the Muslim population of India. In this nationally representative sample of 8436 women, consanguineous marriages accounted for 220 per cent of the total. No differences between the consanguineous and non-consanguineous groups were observed in terms of mean age at marriage or mean age at cohabitation. The study confirmed the negative association between consanguineous marriage and maternal education but also indicated that women in consanguineous unions were more likely to be employed, albeit mainly in agricultural work on behalf of the family. Consanguineous couples more frequently lived in smaller towns and in an extended family environment. Somewhat conflicting results were obtained with indicators of socioeconomic status, but the overall picture suggested that consanguineous households had greater access to consumer goods because of their larger number of co-resident persons.